A STUDY OF THE NEUROTROPIC TENDENCY IN STRAINS OF THE VIRUS OF EPIDEMIC INFLUENZA - Francis, Thomas (The Rockefeller University Press, 1940)
The demonstration by Stuart-Harris that the W.S. strain of epidemic influenza virus can induce a fatal nervous disease in mice has been confirmed. In contrast, however, no previous period of adaptation to chick embryonic brain was required. By serial brain to brain passages in mice originally inoculated with the virus cultivated in the usual chick embryo culture medium a fatal disease, essentially meningeal in character, is produced. The Melbourne strain has been similarly enhanced while other strains have failed to reveal any neurotropic tendencies. The evidence indicates that the neurotropic characteristic is present in the two strains as an inherent quality which is quantitatively heightened and does not represent the acquisition of a property not previously present.